Dr. Packianathan "Chella" Chelladurai: An Eminent Scholar in Sport Management. [Dr. Packianathan "Chella" Chelladurai: Un eminente académico en gestión deportiva]. - Donna L. Pastore (Ramón Cantó Alcaraz, 2014)
Dr. Packianathan "Chella" Chelladurai has a long and distinguished career in sport management and is a recognized scholar of management science. Chella received his Bachelor's and Doctor of Physical Education degrees from the University of Madras, India. He was a member of the All Star Basketball Team of India and coached several basketball teams. Chella left India to pursue graduate studies in Canada. He received a Master's degree in physical education from the University of Western Ontario, and an additional Master's degree from the University of Waterloo. Chella further pursued his Ph.D in management science as well from the University of Waterloo. Chella served on the faculty of the University of Western Ontario from 1971 to 1991. He then joined the faculty at The Ohio State University from 1991 until his retirement in 2012. Currently, Chella is a Distinguished Professor of Sport Management at Troy University.